Physical fitness of Filipino youth in the Western Visayas region and their implication for programs of youth and sport development - Ramos, Ma. Dolores (1980)
The Problem. This study looked into the existing physical fitness status of Filipino college students from state and private colleges in the Western Visayan region in order to relate it to national development goals. Specifically, this study attempted to: 1. Develop a theoretical body of knowledge on physical fitness activities and programs as reviewed from published related literature and studies both here and abroad; 2. Determine the physical performance level of youth in the Western Visayan region, and assess this within the established frame of reference; a. Identify the areas of physical fitness strengths and deficiencies found among college students in the Western Visayan region; b. Test the performance level of the different age and sex groups of college students in deficiencies identified in the study but mainly to meet the needs and development potential of college students in the Western Visayan region; 6. Evolve and propose a Physical Fitness Supplemental Teaching Handbook to update the Physical Education curriculum and at the same time to enrich it according to the physical fitness needs of the Filipino youth in the Western Visayan region. Significance of the study: Essentially and principally, this study provided policy guidelines for national, regional and institutional programs of the department of Education and Culture on Youth and Sports Development in the Western Visayan region and the country as a whole. It aimed to serve different levels and positions in the education hierarchy. For the administrator of the college, either state or private, the data gathered provide bases for a good physical fitness program necessary and required for college students. Likewise, the study provides baseline data for funding and budgeting purposes and for planning educational strategies and innovations related to the physical education program. Moreover, it serves to guide and direct faculty development and improvement in teaching for physical fitness. For the curriculist, the data can provide direction toward which the physical education curriculum can center on. Educational policies and courses of study and textbooks on the subject area can be based on the findings. For the Department of Education and Culture, the study has provided regional norms that point out the minimum requirements of college students. It has also provided a framework of source materials relevant to its program of youth and sports development. For the Department of Youth and sport development, it provided materials necessary in mapping out long range sports programs to improve athletics performance in national and international competition. For the teachers and students of physical education, it provided a body of knowledge related to objectives, content, methods and evaluation of the physical education program. For colleges in Asia and developing nations this study provided a body of knowledge for the improvement and revitalization of the physical education program in relation to national development.
Dissertation (Doctor of philosophy - Philippine Studies). -- [Quezon City] : U.P. College of Education, March 1980.